Sesquicarbene complexes: Bonding at the interface between M-C single bonds and M═C double bonds - Mulks, Florian; Hashmi, A. Stephen K.; Faraji, Shirin (Organometallics, 2020)
Allylic dimetalated complexes [M2C(vinyl)]+ (M = Au(IPr) and Cr(CO)5−) incorporate a new coordination mode of carbon. Digold complexes of this type have recently been detected experimentally. The intrinsic bond orbitals, partial charges, and structural parameters of the gold complexes and of chromium analogs were studied computationally and compared to those of the respective monometalated species and hydrocarbons. This showed that such digold complexes have a carbene character at both Au−C bonds comparable to typical carbene complexes of gold. Dichromium complexes with their stronger π-backdonation compete for interaction with carbon’s π-orbital; each of the chromium atoms partakes in double bonding that is signiﬁcant but weaker than that in the carbene analogs. Containing two M−C bonds on the interface between single and double bonds, these bridged complexes can be conceived as “sesquicarbene complexes”. The π-system acted in a very adaptive manner and employed additional stabilization of the vinyl system only where needed. Signiﬁcant carbene character is found simultaneously in both M−C bonds at the same carbon center. The discovery of these complexes with relatively strong double bond character between one carbon and two metal atoms could bring unusual single-carbon-centered organometallic cascade reactions to the horizon.